Efek Moderasi EPS dalam Pengaruh DER dan ROA terhadap Harga Saham di Indeks LQ45 - Doni Yusuf Bagaskara; Rohmadi Rohmadi (Universitas 45 Surabaya, 2024)
This study aims to determine the Moderation Effect of EPS in the effect of DER and ROA on Stock Prices in the LQ45 Index. This study uses quantitative methods, the study population is 45 issuers in the LQ45 Index, the research sample comes from 2022 data. Researchers used data collection models and documents from the Indonesia Stock Exchange (IDX). The analysis process uses cross section multiple regression analysis assisted by JASP version 0.18.1. The results of this study state that DER has no effect on stock price, ROA has a significant negative effect on stock price, and EPS cannot moderate the relationship between DER and stock price, and EPS can moderate the relationship between ROA and stock price. Research findings can have an impact on investor decision considerations in looking at stock price movements.